2021
DOI: 10.1017/s0033291721001720
|View full text |Cite
|
Sign up to set email alerts
|

Genetic contributions to suicidal thoughts and behaviors

Abstract: Suicidal ideation, suicide attempt (SA) and suicide are significantly heritable phenotypes. However, the extent to which these phenotypes share genetic architecture is unclear. This question is of great relevance to determining key risk factors for suicide, and to alleviate the societal burden of suicidal thoughts and behaviors (STBs). To help address the question of heterogeneity, consortia efforts have recently shifted from a focus on suicide within the context of major psychopathology (e.g. major depressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 75 publications
2
35
0
Order By: Relevance
“…Significant genetic correlations have been validated by our results between depression and psychiatric traits (anxiety and suicidal ideation) (70; 27) We also identified links connecting depression with GORD, BMI, chronic gastritis, and osteoarthrosis, reinforcing the complexity of depression’s etiology. Strong clinical relationships between the digestive system and psychiatric conditions have been known for over 35 years (31; 100).…”
Section: Discussionsupporting
confidence: 69%
“…Significant genetic correlations have been validated by our results between depression and psychiatric traits (anxiety and suicidal ideation) (70; 27) We also identified links connecting depression with GORD, BMI, chronic gastritis, and osteoarthrosis, reinforcing the complexity of depression’s etiology. Strong clinical relationships between the digestive system and psychiatric conditions have been known for over 35 years (31; 100).…”
Section: Discussionsupporting
confidence: 69%
“…Familial and genetic predisposition is identified as a contributing factor to suicide behaviors. Suicidal thoughts and behaviors are moderately heritable, with a significant proportion of risk attributed to genetic variation (DiBlasi et al, 2021). Familial research has reported that genetic variation is significantly contributing to suicidal thoughts and behaviors (DiBlasi et al, 2021).…”
Section: Figure1 Biological Risk Factors In Suicidementioning
confidence: 99%
“…Suicidal thoughts and behaviors are moderately heritable, with a significant proportion of risk attributed to genetic variation (DiBlasi et al, 2021). Familial research has reported that genetic variation is significantly contributing to suicidal thoughts and behaviors (DiBlasi et al, 2021). Besides, suicide attempts are transmitted independently of psychiatric comorbidities (DiBlasi et al, 2021;Turecki et al, 2019).…”
Section: Figure1 Biological Risk Factors In Suicidementioning
confidence: 99%
See 1 more Smart Citation
“…A published "road map" for genetic counseling in psychiatry explains this well (Austin, 2020). For both polygenic risks and more specific risk genes or gene pathways, for the foreseeable future, the effect on the risk of suicidal behavior for a specific individual will be almost infinitesimally small, given complex interactions with other individual-specific genetic factors and environmental risks (DiBlasi, Kang, & Docherty, 2021).…”
Section: Risk Misinterpretationmentioning
confidence: 99%